Status Hak Waris Anak di Luar Nikah Menurut Kompilasi Hukum Islam Dengan Hukum Perdata (Studi Kasus Di PA Dan PN Tanjung Karang) - Kamsari (Law Faculty of Universitas Bandar Lampung, 2012)
Heir system represent one of the way of the existence of evacuation of is ownership of that is making a move good and chattel and rights of materil of side endowing after pertinent pass away. One of [the] problem of hereditary law exist in indonesia is to regarding child outside marrying, where there are elementary between law of islam and with civilÂ in this writing how child heir rights status outside marrying according to complilation punish islam and according to civil law reaserch this use method approach of empiric and normatif, source of data of sekunder Data collecting primary data and done with bibliography study and field study and analysis qualitative. Result of research indicate that child heir rights status outside marrying which there are in compilationb punish islam is that the child only is entitled to inherit from its mother and its mother family and so do on the contrary in civil law. to its father of the child him is not at all generate relation is inheriting each other. In civil law arise after existence of confession of woman or men which him after existence of authentication.